Pengaruh Disiplin Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum dan Penataan Ruang Provinsi Sumatera Utara - Kurniawan, Adinda Putri; Wahyuni, Neni Sri; Sonata, Ilham (Universitas Medan Area, 2025)
The purpose of this study is to determine the influence of work discipline and job satisfaction on employee performance at the Public Works and Spatial Planning Department of North Sumatra Province. This research method is quantitative. Using the Slovin formula, 72 respondents were obtained as a sample from a population of 263 people. Interviews and questionnaires were used to collect data. This study used multiple linear regression analysis. The results of this research are: (1) Work discipline has a positive and significant influence on employee performance at the Public Works and Spatial Planning Department of North Sumatra Province, (2) Job satisfaction has a positive and significant influence on employee performance at the Public Works and Spatial Planning Department of North Sumatra Province, (3) Work discipline and job satisfaction have a positive and significant influence on employee performance at the Public Works and Spatial Planning Department of North Sumatra Province.